Hubungan Karakteristik dan Aktivitas Komunikasi dengan Perilaku Masyarakat Perkampungan Budaya Betawi - U. Astuti; A.V.S. Hubeis; F. Rohadji; S. Riyanto (Institut Pertanian Bogor, 2008)
In 10 March 2005 Parlement DKI Jakarta area have approved of Regional lawing proposal number 3/2005 a boutBetawi Cultural Civilization in Jagakarsa district South Jakarta. The aim of Betawi Cultural Civilization the makecommunity a ware style life Betawi Cultural in to protect enviroment and building Betawi. This Research aimed atdescribe civilazation characteristic communication activity and community behavior and analityng relationcivilization which conducted in July – Agust 2006 using relation discribtive method. The Result so may individucharacteristic significanly related with community behavior such as formal education with knowledge nonformal withattitude and action, while the communication community correlated with community behavior are exsposenewspapaer, exspose with knowledge, interpersonal communication exspose with attitude.